Construction of Functional Materials in Various Material Forms from Cellulosic Cholesteric Liquid Crystals - Kazuma Miyagi; Yoshikuni Teramoto (Nanomaterials, 2021)
Wide use of bio-based polymers could play a key role in facilitating a more sustainable society because such polymers are renewable and ecofriendly. Cellulose is a representative bio-based polymer and has been used in various materials. To further expand the application of cellulose, it is crucial to develop functional materials utilizing cellulosic physicochemical properties that are acknowledged but insufficiently applied. Cellulose derivatives and cellulose nanocrystals exhibit a cholesteric liquid crystal (ChLC) property based on rigidity and chirality, and this property is promising for constructing next-generation functional materials. The form of such materials is an important factor because material form is closely related with function. To date, researchers have reported cellulosic ChLC materials with a wide range of material forms—such as films, gels, mesoporous materials, and emulsions—for diverse functions. We first briefly review the fundamental aspects of cellulosic ChLCs. Then we comprehensively review research on cellulosic ChLC functional materials in terms of their material forms. Thus, this review provides insights into the creation of novel cellulosic ChLC functional materials based on material form designed toward the expanded application of cellulosics.